Innovation, science, environment, special edition : charting sustainable development in Canada, 1987-2007 - Meadowcroft, James; Toner, Glen, 1952- (Innovation, science, environment series ;, 2009)
Analyses a number of dimensions of the Canadian experience in implementing sustainable development. This title discusses both the breakthroughs and disappointments of the Canadian experience, and looks toward the future to discuss what additional steps need to be undertaken domestically if Canada is to once again achieve a position of leadership.